AIDS sourcebook : basic consumer health information about the human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS), including facts about its origins, stages, types, transmission, risk factors, and prevention, and featuring details about diagnostic testing, antiretroviral treatments, and co-occurring infections, such as Cytomegalovirus, Mycobacterium Avium Complex, Pneumocystis Carinii Pneumonia, and Toxoplasmosis; along with tips for living with HIV/AIDS, updated statistics, reports on current research initiatives, a glossary of related terms, and a list of resources for additional help and information. - Omnigraphics, Inc. (2018)
"Provides consumer health information about transmission, testing, stages, and treatment of human immunodeficiency virus (HIV), with facts about prevention, related complications, and tips for living with HIV/AIDS. Includes index, glossary of related terms, directory of resources and online access"--
Includes bibliographical references and index.
Keywords: AIDS (Disease) -- Popular works